2021
DOI: 10.3389/fpsyg.2021.647972
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of Uncertainty and Fear of COVID-19 Moderating Role in Relationship Between Job Insecurity and Work-Related Distress in the Republic of Serbia

Abstract: The COVID-19 outbreak in Serbia was followed by strict restrictions that negatively affected the economy, particularly small size companies. The complete lockdown and the prohibition of certain services have led to an unstable employment situation. Only several studies investigated the job insecurity and its consequences during COVID-19 pandemic, and some of them highlight the fear of COVID-19 as a significant moderator of mental health. Other studies emphasize the huge effect that intolerance of uncertainty c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
4
25
1
Order By: Relevance
“…Unlike other related epidemics and disasters, the outbreak has touched upon all frontiers – personal, social, monetary, physiological (Aguiar-Quintana et al, 2021 ; Godinic et al, 2020 ). Contrary to our assumption that the fear brought on by the pandemic will increase the job insecurity, we were not able to establish statistically significant relationship between the two, which is at odds with findings gathered by Blanuša et al ( 2021 ) and Ruffolo et al ( 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike other related epidemics and disasters, the outbreak has touched upon all frontiers – personal, social, monetary, physiological (Aguiar-Quintana et al, 2021 ; Godinic et al, 2020 ). Contrary to our assumption that the fear brought on by the pandemic will increase the job insecurity, we were not able to establish statistically significant relationship between the two, which is at odds with findings gathered by Blanuša et al ( 2021 ) and Ruffolo et al ( 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…However, excessive fear may paralyze and lead to personality collapse, wherein each action may seem futile and meaningless. There is now already extensive empirical support for the claim that job uncertainty during COVID-19 leads to strain and depression (Blanuša et al, 2021 ; Godinic et al, 2020 ; Nelson & Kaminsky, 2020 ). Hypothesis 4: The fear of COVID-19 leads to depression Hypothesis 5: The fear of COVID-19 leads to anxiety …”
Section: Theory and Model Developmentmentioning
confidence: 99%
“…The findings are consistent with cross-national evidence on adverse mental health outcomes generated during the assessment of coronavirus uncertainty repercussions (Godinic et al, 2020;Aguiar-Quintana et al, 2021;Blanuša et al, 2021;Ganson et al, 2021;Ruffolo et al, 2021). Blanuša et al (2021) found that the distress increases proportionately to the rise of job uncertainty and fear of COVID-19. Nelson and Kaminsky (2020) asserted that the ongoing crisis concerning health and social and monetary security significantly contributes to intense anxiety and depression.…”
Section: Discussionsupporting
confidence: 85%
“…There is lack of support in the literature that would explain how exposure to hazard-related information influences the formation of adaptive or maladaptive coping strategies of employees aimed at psychological well-being retention. Also, although many studies have previously corroborated that uncertainty influences psychosocial and occupational functioning (Aguiar-Quintana et al, 2021 ; Blanuša et al, 2021 ; Ganson et al, 2021 ; Ruffolo et al, 2021 ), there are not many studies in the field of occupational psychology examining how job uncertainty leads to protective motivation when EPPM perpetuates the insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…No studies have focused on the relationship between variance in workload and depressive and anxiety symptoms, and a few studies have focused on the relationship between job future ambiguity and depressive and anxiety symptoms during the COVID-19 pandemic. A study in Serbia among different categories of employees, demonstrated that job uncertainty and the fear of COVID-19 related to work-related distress [ 48 ]. In the U.S.A., another study among white-collar employees indicated that job insecurity has a substantial impact on depressive and anxiety symptoms, [ 49 ].…”
Section: Discussionmentioning
confidence: 99%